Shortened immunotherapy dose‐escalation saves time, but is it safe? A case‐control study comparing the rates of adverse reactions between conventional and fast‐escalation subcutaneous immunotherapy protocols during the induction phase. Issue 6 (17th September 2020) - Herrmann, Ina; Loft, Klaus E.; Olivry, Thierry
Abstract : Background: Allergen immunotherapy (AIT) is the only intervention believed to change the course of atopic diseases. As dogs appear to have fewer severe adverse events (AEs) compared to people receiving AIT, a prolonged dose‐escalation induction phase might not be needed. Objectives: To report the incidence and characteristics of AEs induced by a fast‐escalation subcutaneous immunotherapy (f‐SCIT) protocol compared to a conventional (c‐SCIT) regimen. Animals: One hundred dogs treated with either f‐ SCIT (Centre 1, 50 dogs) or c‐SCIT (Centre 2, 50 dogs). Methods and materials: A case‐control study retrospectively evaluating AEs during the induction of AIT. We determined the incidence and type of AEs in each SCIT group; we also assessed factors such as self‐limitation and the need for AE‐associated protocol changes. Results: Twelve of 100 dogs (12%) developed a SCIT‐attributable AE during the induction phase, with one dog having a local and 11 having systemic reactions (nine Grade I, two Grade II, none of grades III or IV). Dogs treated with the f‐SCIT had a significantly higher rate of AEs (11 of 50; 22%) compared to those receiving the c‐SCIT (one of 50; 2%). Most of the AEs (10 of 11; 91%) in the f‐SCIT group were mild and self‐limiting. Conclusions and clinical importance: The induction phase of f‐SCIT is simpler, and the maintenance phase is reached faster than that of the c‐SCIT. Despite its higher rate of AEs than with the c‐SCIT regimen, the majority of f‐SCIT‐associated AEs were mild and self‐limiting. Whether or not this f‐SCIT protocol leads to a faster time‐to‐efficacy needs to be determined. Abstract : Background – Allergen immunotherapy (AIT) is the only intervention believed to change the course of atopic diseases. As dogs appear to have fewer severe adverse events (AEs) compared to people receiving AIT, a prolonged dose‐escalation induction phase might not be needed. Objectives – To report the incidence and characteristics of AEs induced by a fast‐escalation subcutaneous immunotherapy (f‐SCIT) protocol compared to a conventional (c‐SCIT) regimen. Conclusions and clinical importance – The induction phase of f‐SCIT is simpler, and the maintenance phase is reached faster than that of the c‐SCIT. Despite its higher rate of AEs than with the c‐SCIT regimen, the majority of f‐SCIT‐associated AEs were mild and self‐limiting. Whether or not this f‐SCIT protocol leads to a faster time‐to‐efficacy needs to be determined. Résumé: Contexte: L'immunothérapie allergénique (AIT) est le seul moyen supposé capable de changer l'évolution des maladies atopiques. Les chiens semblent avoir peu d'effets secondaires (AEs) comparé à l'homme, une phase d'induction à doses croissantes pourrait être inutile. Objectifs: Décrire l'incidence et les caractéristiques des AEs dus à l'immunothérapie sous cutanée à induction rapide (f‐SCIT) comparé à un traitement conventionnel (c‐SCIT). Sujets: Cent chiens traités soit par f‐SCIT (Centre 1, 50 chiens) ou c‐SCIT (Centre 2, 50 chiens). Matériels et méthodes: Une étude contrôle rétrospective évaluant les AEs au cours de l'induction de AIT. Nous avons déterminé l'incidence et le type d'AEs dans chaque groupe SCIT ; nous déterminons aussi les facteurs tels que la guérison spontanée et le besoin de changer les protocoles associés aux AE. Résultats: Douze des 100 chiens (12%) ont développés des AE attribuables à SCIT au cours de la phase d'induction, avec réaction locale chez un chien et réactions systémiques chez 11 chiens (neuf Grade I, deux Grade II, aucun grades III ou IV). Les chiens traités avec f‐SCIT avaient un taux significativement plus élevé d'AEs (11 sur 50; 22%) comparé à ceux recevant c‐SCIT (un sur 50; 2%). La plupart des AEs (10 sur 11; 91%) dans le groupe f‐SCIT étaient modérés et spontanément contrôlés. Conclusions et importance clinique: La phase d'induction de f‐SCIT est simple et la phase de maintenance est atteinte plus rapidement que celle de c‐SCIT. Malgré leur taux élevé, la majorité des AEs associés à f‐SCIT étaient modérés et auto‐résolutifs. Il faut encore déterminer si ce protocole mène à une efficacité clinique plus rapide. RESUMEN: Introducción: la inmunoterapia con alérgenos (AIT) es la única intervención que se cree que cambia el curso de las enfermedades atópicas. Dado que los perros parecen tener menos eventos adversos graves (AEs) en comparación con las personas que reciben AIT, es posible que no sea necesaria una fase de inducción de aumento de dosis prolongada. Objetivos: reportar la incidencia y las características de los AEs inducidas por un protocolo de inmunoterapia subcutánea escalonada rápida (f‐SCIT) en comparación con un régimen convencional (c‐SCIT). Animales: Cien perros tratados con f‐SCIT (Centro 1, 50 perros) o c‐SCIT (Centro 2, 50 perros). Métodos y materiales: un estudio de casos con controles que evaluó retrospectivamente los AEs durante la inducción de la AIT. Determinamos la incidencia y el tipo de AEs en cada grupo de SCIT; también evaluamos factores como la autolimitación y la necesidad de cambios de protocolo asociados a AEs. Resultados: doce de 100 perros (12%) desarrollaron un AE atribuible a SCIT durante la fase de inducción, con un perro con reacciones locales y 11 con reacciones sistémicas (nueve de grado I, dos de grado II, ninguno de grado III o IV). Los perros tratados con f‐SCIT tuvieron una tasa significativamente mayor de AEs (11 de 50; 22%) en comparación con los que recibieron c‐SCIT (uno de 50; 2%). La mayoría de los AEs (10 de 11; 91%) en el grupo de f‐SCIT fueron leves y autolimitantes. Conclusiones e importancia clínica: la fase de inducción de la f‐SCIT es más simple y la fase de mantenimiento se alcanza más rápido que con la c‐SCIT. A pesar de su mayor tasa de AEs que con el régimen de c‐SCIT, la mayoría de los AEs asociados con la f‐SCIT fueron leves y autolimitantes. Se debe determinar si este protocolo f‐SCIT induce tratamiento efectivo más rápido. Zusammenfassung: Hintergrund: Die Allergenimmuntherapie (AIT) ist die einzige Intervention, von der man glaubt, dass sie den Verlauf der atopischen Erkrankung beeinflussen kann. Da Hunde scheinbar weniger Nebenwirkungen (AEs) als Menschen, die AIT erhalten, haben, könnte es möglich sein, dass eine verlängerte Dosis‐Eskalations Induktionsphase nicht benötigt wird. Ziele: Ein Bericht über das Auftreten und die Charakteristika der AEs, die durch das Protokoll einer subkutanen Schnell‐Eskalations Immuntherapie (f‐SCIT) im Vergleich zu einem konventionellen (c‐SCIT) Regime ausgelöst werden. Tiere: Einhundert Hunde, die entweder mit f‐SCIT (Zentrum 1, 50 Hunde) oder c‐SCIT (Zentrum 2, 50 Hunde) behandelt wurden. Methoden und Materialien: Eine Fall‐Kontrollstudie, die retrospektiv die AEs während der Induktionsphase des AIT evaluierte. Wir bestimmten die Häufigkeit und den Typ der AEs einer jeden SCIT Gruppe; wir erfassten ebenso Faktoren wie Selbst‐Limitierung und den Bedarf einer AE‐assoziierten Protokolländerung. Ergebnisse: Zwölf von 100 Hunden (12%) entwickelten SCIT‐zuordenbare AEs während der Einleitungsphase, wobei ein Hund eine lokale und 11 eine systemische Reaktion hatten (neun Grad I, zwei Grad II, keine Grad III oder IV). Hunde, die mit einer f‐SCIT behandelt wurden, hatten eine signifikant höhere Rate an AEs (11 von 50; 22%) im Vergleich zu jenen, die c‐SCIT erhielten (einer von 50; 2%). Die meisten AEs (10 von 11; 91%) in der f‐SCIT Gruppe waren mild und selbstlimitierend. Schlussfolgerungen und klinische Bedeutung: Die Einleitungsphase von f‐SCIT ist einfacher und die Erhaltungsphase wird rascher erreicht als mit c‐SCIT. Trotz der höheren Zahlen an AEs mit dem c‐SCIT Regime, waren die Mehrheit der f‐SCIT‐assoziierten AEs mild und selbstlimitierend. Ob das f‐SCIT Protokol zu einem rascheren Wirkungseintritt führt, muss noch bestimmt werden. Resumo: Contexto: A imunoterapia com alérgenos (ITA) é a única intervenção em que se acredita que seja possível modificar curso das doenças atópicas. Como os cães parecem apresentar menos eventos adversos graves (EAs) em comparação com pessoas que recebem ITA, uma fase de indução com escalonamento de dose prolongada pode não ser necessária. Objetivos: Relatar a incidência e as características dos EAs induzidos por um protocolo de imunoterapia subcutânea de escalonamento rápido (f‐SCIT) em comparação com um regime convencional (c‐SCIT). Animais: Cem cães tratados com f‐SCIT (Centro 1, 50 cães) ou c‐SCIT (Centro 2, 50 cães). Métodos e materiais: Um estudo de caso‐controle avaliando retrospectivamente EAs durante a indução de ITA. Determinamos a incidência e o tipo de EAs em cada grupo SCIT; também avaliamos fatores como autolimitação e a necessidade de mudanças no protocolo associado ao EA. Resultados: Doze de 100 cães (12%) desenvolveram um EA atribuível à SCIT durante a fase de indução, com um cão tendo uma reação local e 11 tendo reações sistêmicas (nove Grau I, dois Grau II, nenhum dos graus III ou IV). Os cães tratados com o f‐SCIT tiveram uma taxa significativamente maior de EAs (11 de 50; 22%) em comparação com aqueles que receberam o c‐SCIT (um de 50; 2%). A maioria dos EAs (10 de 11; 91%) no grupo f‐SCIT foram leves e autolimitados. Conclusões e importância clínica: A fase de indução do f‐SCIT é mais simples, e a fase de manutenção é alcançada mais rapidamente que a do c‐SCIT. Apesar de sua taxa mais alta de EAs do que com o regime c‐SCIT, a maioria dos EAs associados à f‐SCIT foram leves e autolimitados. Se este protocolo f‐SCIT leva ou não a um tempo de eficácia mais rápido, precisa ser determinado. 要約: 背景: アレルゲン免疫療法（AIT）は、アトピー性疾患の推移を変えると考えられている唯一の介入である。犬はAITで治療している人と比較して重篤な有害事象（AE）が少ないように見えるため、長期用量漸増誘導期は必要ない可能性がある。 目的: 本研究の目的は、従来の（c‐SCIT）レジメと比較した、急速段階的な皮下免疫療法（f‐SCIT）プロトコルによって引き起こされるAEの発生率と特性を報告することであった。 被験動物: f‐SCIT（センター1、50頭）またはc‐SCIT（センター2、50頭）のいずれかで治療された100頭の犬。 材料と方法: 本研究はAIT誘発中のAEを遡及的に評価する症例対照研究であった。各SCIT群のAE発生率および種類を決定した。また、自己制限やAE関連のプロトコル変更の必要性などの要因も評価した。 結果: 犬100頭のうち12頭（12％）が導入期にSCITに起因したAEを発症し、そのうち1頭が局所反応を示し、11頭が全身反応を示した（グレードIが9頭、グレードIIが2頭、グレードIIIまたはIVのいずれもなし）。 f‐SCIT治療犬（50頭のうち11頭; 22％）は、c‐SCIT治療犬（50頭のうち1頭; 2％）と比較して、有意に高いAE率を示した。 f‐SCIT群のほとんどのAE（11頭のうち10頭; 91％）は軽度で自己制限的であった。 結論と臨床的重要性: f‐SCITの導入期はc‐SCITよりも単純で、維持期に早く到達する。 c‐SCITレジメよりもAEの発生率が高いにもかかわらず、f‐SCIT関連のAEの大部分は軽度で自己制限的であった。本研究のf‐SCITプロトコルが、より早期の有効性につながるかどうかを判断する必要がある。 摘要: 背景: 过敏原免疫治疗(AIT)是唯一被认为改变异位性疾病病程的疗法。与接受AIT的病人相比，犬的严重不良反应(AEs)似乎较少，因此可能不需要长时间的剂量递增诱导期。 目的: 报告与传统(c‐SCIT)方案相比，快速递增皮下免疫治疗(f‐SCIT)方案诱导的AE发生率和特征。 动物: 100只犬接受f‐SCIT（中心1，50只犬）或c‐SCIT（中心2，50只犬）给药。 方法和材料: 回顾性评价AIT诱导期间AE的病例对照研究。我们确定了每个SCIT组中AE的发生率和类型；我们还评估自限性和AE相关方案变更需求等因素。 结果: 100只犬中有12只(12%)在诱导阶段发生SCIT引起的AE，其中1只犬出现局部反应，11只犬出现全身反应（9只为I级，2只为II级，无III级或IV级反应）。接受f‐SCIT治疗的犬的AE发生率(11/50；22%)显著高于接受c‐SCIT治疗的犬(1/50；2%)。f‐SCIT组的大多数AE(10/11；91%)是轻度和自限性的。 结论和临床重要性: f‐SCIT的诱导期更简单，且比c‐SCIT更快达到维持期。尽管其AE发生率高于c‐SCIT方案，但大多数f‐SCIT相关AE是轻度和自限性的。需要确定该f‐SCIT方案的起效时间是否更快。